Human microRNA‐298 plays a vital role in maintaining APP and tau homeostasis and IL‐induced inflammation: Implication in Alzheimer's disease. (20th December 2022) - Wang, Ruizhi; Maloney, Bryan; Long, Justin M; Sambamurti, Kumar; Counts, Scott E.; Lahiri, Debomoy K
Abstract: Background: Alzheimer's disease (AD) is marked by neurofibrillary tangles mainly composed of hyperphosphorylated microtubule‐associated protein tau; senile plaques comprising amyloid β (Aβ) peptides; and neuroinflammation. How these pathological changes are regulated remains unclear. Genetic, epigenetic, and environmental factors play important roles in disease progression. MicroRNA (miRNA), a group of small non‐coding RNAs, regulates multiple biological and pathological processes by binding to target mRNAs and altering translation levels. Disrupting this process could contribute to AD pathogenesis. We hypothesize that miR‐298 plays a vital role in maintaining APP and tau homeostasis and IL‐induced inflammation, particularly gliosis. Method: We performed miR‐298 treatments and blockade by antisense‐miR298 (antagomiRs) in 3'UTR‐ reporter clone ‐transfected cultures and protein levels from target native mRNAs (Chopra et al‐ Mol. Psychiatry ‐2021). We transfected human astrocyte cells with miR‐298 mimics or antagomiRs. We analyzed culture media and lysates for protein and mRNA. We performed ELISA and real‐time‐qPCR assays to determine cytokines, APP and tau levels. We analyzed autopsy brain tissues from non‐cognitively impaired (NCI) and AD subjects by measuring levels of miR‐298, target mRNAs and proteins in cortical samples, as we described (Wang et al‐ Mol. Psychiatry ‐2022). Result: We identified putative sites for miR‐298 in mRNAs encoding APP, BACE1, MAPT, IL1α, and IL6. Treatment by miR‐298 significantly increased production and secretion of multiple pro‐inflammatory cytokines, specifically IL‐1, IL‐6 and TNF‐α in human astrocyte cultures. Furthermore, treatment by miR‐298 reduced tau, APP and BACE1 protein and mRNA levels in astrocyte cultures. Levels of miR‐298 varied in postmortem human temporal lobe between AD patients and age‐matched NCI controls. Conclusion: MiR‐298 induced a variety of pro‐inflammatory cytokines without administration of other challenges. Induction of multiple cytokines may be due to combinations of direct miRNA activity and regulation of upstream signaling pathways. MiR‐298 may play an important biological role in AD by reducing APP, BACE1 and tau expression while increasing the physiologic production of IL cytokines. This apparent paradox is resolved by noting that early‐stage (prodromal) gliosis may contribute to the clearance of toxic aggregates. We plan to test miR‐298 in AD animal models, including human tau‐overexpressing transgenic mice. We appreciate NIH‐NIA grants: (R01AG051086, R21AG056007, R56AG072810, P01AG014449, P30AG072976).